Short-type single-balloon enteroscope-assisted ERCP in postsurgical altered anatomy: potential factors affecting procedural failure - Yane, Kei; Katanuma, Akio; Maguchi, Hiroyuki; Takahashi, Kuniyuki; Kin, Toshifumi; Ikarashi, Satoshi; Sano, Itsuki; Yamazaki, Hajime; Kitagawa, Koh; Yokoyama, Kensuke; Koga, Hideaki; Nagai, Kazumasa; Nojima, Masanori (Endoscopy, 2017)
Background and study aims Short-type single-balloon enteroscope (short SBE)-assisted endoscopic retrograde cholangiopancreatography (ERCP) is a promising alternative treatment in postsurgical altered anatomy. However, it is technically demanding, and factors affecting its technical difficulty have not yet been clarified. This study aimed to examine the procedural success rate of short SBE-assisted ERCP and the potential factors affecting procedural failure.Patients and methods A total of 117 consecutive patients (203 procedures) with surgically altered anatomy underwent ERCP using prototype short SBEs. The procedural success rate of short SBE-assisted ERCP and the potential factors affecting procedural failure were examined retrospectively.Results The enteroscopy success rate and procedural success rate were 92.6 % (95 % confidence interval [CI] 88.1 % – 95.8 %) and 81.8 % (95 %CI 75.8 % – 86.8 %), respectively. Multivariate analyses indicated that pancreatic indication (odds ratio [OR] 4.35, 95 %CI 1.67 – 11.4), first ERCP attempt (OR 6.03, 95 %CI 2.17 – 16.8), and no transparent hood (OR 4.61, 95 %CI 1.48 – 14.3) were potential risk factors for procedural failure.Conclusions Short SBE-assisted ERCP was effective in postsurgical altered anatomy. This large case series suggested the potential factors affecting procedural failure.